2017
DOI: 10.14744/nci.2017.82787
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum vitamin B12 levels and frailty in older adults

Abstract: OBJECTIVE:Frailty is associated with recurrent falls, fractures, limitation of daily living activities, cognitive impairment, increase in hospitalization, placement in nursing home, and mortality rate in older adults. Although malnutrition is one of the most important etiological factors, role of micronutrients is unclear. The aim of this study was to investigate association between frailty and vitamin B12, which has been demonstrated to be related to numerous geriatric syndromes.METHODS:Total of 335 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 23 publications
6
17
0
1
Order By: Relevance
“…22 In a study carried out in Turkey, the prevalence of frailty was found to be 26.3% in individuals aged >65 years. 12 Similarly, the prevalence of frailty in the present study was 25.7%. It is known that frailty is more common in women.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…22 In a study carried out in Turkey, the prevalence of frailty was found to be 26.3% in individuals aged >65 years. 12 Similarly, the prevalence of frailty in the present study was 25.7%. It is known that frailty is more common in women.…”
Section: Discussionsupporting
confidence: 69%
“…Although the prevalence of frailty varies according to the scales used, it is between 7% and 12% among individuals aged >65 years . In a study carried out in Turkey, the prevalence of frailty was found to be 26.3% in individuals aged >65 years . Similarly, the prevalence of frailty in the present study was 25.7%.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations